Development of NAPZA E-LKPD based on Problem to Improve Collaboration and Problem Solving Abilities of High School Students - Marcelia Ardianti; Sigit Saptono (Universitas Negeri Semarang, 2024)
In learning material about NAPZA, learning media that involve collaborative process among students to solve issues related to drug misuse is essential during high school education. The existing NAPZA abuse learning media at SMA N 1 Slawi have been found to be limited in terms of contextual relevance and student engagement in collaborative problem-solving activities. Thus, there is a need to develop problem-based learning media for NAPZA material. This study aims to analyze the validity of the content and media of the E-LKPD product, as well as assess the improvement in collaboration and problem-solving abilities of high school students using the NAPZA E-LKPD based on problem. This research was conducted at Senior High School 1 Slawi even semester. The research adopts a research and development method, following the ADDIE model (analyze, design, development, implementation, and evaluation). NAPZA E-LKPD based on problem was declared highly valid with an assessment of 98.64% by media experts and 97.58% by material experts. Based on the result of this research, NAPZA E-LKPD based on problem proves to enhance students' collaboration abillity. Additionally, the E-LKPD NAPZA based on problem significantly improves high school students' problem-solving ability.